Pengaruh Ritualistic Dan Consequential Terhadap Perilaku Konsumen Pada Modest Fashion : Studi Pada Mahasiswi Universitas Sembilanbelas November Kolaka - Tina Tina; Fitri Kumalasari; Ismanto Ismanto (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
The purpose of this Study was to determine: (1)Ritualistic influence on consumer behavior in modest fashion (Study on female students at the University of Nineteen November, Kolaka).(2)Consequential influence on consumer behavior in modest fashion (Study on female students at the University of Nineteen November, Kolaka). This research is a quantitative study with an explanatory research model using a questionnaire as the instrument. The population in this study were all female students at the University of nineteen November Kolaka with a total sample of 110 respondents using purposive sampling.Testing research instrumentusing validity and reability tests with SPSS 25.0. The data analisis technique used in this research is Structural Equating Modeling (SEM) bades on Partial Least Square (PLS) through measurement model testing (outer model) and structural model testing (inner model) with Smart PLS 4.0. The results of this study indicate that the ritualistic variable has a positive and significant effect on consumer behavioras indicated by a P-Value of 0.000 and the Consequential variable also has a positive and significant effect on consumer behavior as indicated by a P-Value of 0.000